A Direct-Learning Approach to Acquiring a Bimanual Tapping Skill. Issue 5 (3rd September 2017) - Michaels, Claire F.; Gomes, Thábata V. B.; Benda, Rodolfo N.
ABSTRACT: The theory of direct learning (D. M. Jacobs & C. F. Michaels, 2007 ) has proven useful in understanding improvement in perception and exploratory action. Here the authors assess its usefulness for understanding the learning of a motor skill, bimanual tapping at a difficult phase relation. Twenty participants attempted to learn to tap with 2 index fingers at 2 Hz with a phase lag of 90° (i.e., with a right-right period of 500 ms and a right-left period of 125 ms). There were 30 trials, each with 50 tapping cycles. Computer-screen feedback informed of errors in both period and phase for each pair of taps. Participants differed dramatically in their success. Learning was assessed by identifying the succession of attractors capturing tapping over the experiment. A few participants' attractors migrated from antiphase to 90° with an appropriate period; others became attracted to a fixed right-left interval, rather than phase, with or without attraction to period. Changes in attractor loci were explained with mixed success by direct learning, inviting elaboration of the theory. The transition to interval attractors was understood as a change in intention, and was remarkable for its indifference to typical bimanual interactions.